Roles of religiosity in enhancing life satisfaction, ethical judgements and consumer loyalty - Ho Phi Dinh; Phuong Van Nguyen; Thi Vu Anh Trinh; Mai Huong Nguyen (Cogent Business & Management, 2022)
Previous research concerning religiosity and consumer behaviors highlights that consumers are possibly affected by religion in areas such as life satisfaction, faith, ethics, and materialism. Analysis, however, has yet to develop a systematic framework that examines the effects of particular religious commitments on consumer behaviors, such as life satisfaction, ethical decisions, and intentions of loyalty, which is the main incentive for us to conduct this research. This study which takes into account Catholic affiliation in the Vietnamese context intends to develop the literature on the relationship between religiosity and consumer behaviors. Specifically, aiming to explore potential mediators in the interrelationship between religious commitments and customer loyalty intentions at convenience stores, the research incorporates ethical judgements and life satisfaction. The Structural Equation Modeling method is utilized to analyze the surveyed data from 388 Catholics for hypothesis testing. According to the tested results, satisfaction with life plays a significant mediating role in the relationship between religious commitments and customer loyalty. On the other hand, ethical judgements serve as an important mediator that considerably enhances the impact of intrinsic religiosity on consumer loyalty. The findings also provide an insightful view of the sociology of religion regarding business enterprises.
Keywords: 650; religiosity; ethical judgment; life satisfaction; loyalty intention; Religious commitment